2016
DOI: 10.1186/s12879-016-1993-1
|View full text |Cite
|
Sign up to set email alerts
|

Infection control and tuberculosis among health care workers in Viet Nam, 2009-2013: a cross-sectional survey

Abstract: BackgroundData on tuberculosis (TB) among health care workers (HCW) and TB infection control (TBIC) indicators are rarely available at national level. We assessed multi-year trends in notification data of TB among HCW and explored possible associations with TBIC indicators.MethodsNotified TB incidence among HCW and 3 other TBIC indicators were collected annually from all 64 provincial and 3 national TB facilities in Vietnam. Time trends in TB notification between 2009 and 2013 were assessed using linear regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…The study identified adherence to N95 respirator use among HCWs serving in MDR-TB wards and in the laboratory, and similar findings were observed in a cross-sectional study among HCWs in Vietnam and India [ 28 ]. Although there was a supply of N95 respirators at the TB specialty hospital, they were not being used in wards with drug-susceptible TB patients.…”
Section: Discussionsupporting
confidence: 60%
“…The study identified adherence to N95 respirator use among HCWs serving in MDR-TB wards and in the laboratory, and similar findings were observed in a cross-sectional study among HCWs in Vietnam and India [ 28 ]. Although there was a supply of N95 respirators at the TB specialty hospital, they were not being used in wards with drug-susceptible TB patients.…”
Section: Discussionsupporting
confidence: 60%
“…These findings are consistent with a similar study by De Perio & Niemeier (2014) who observed that there was an increased risk of tuberculosis transmission when health workers practiced inadequate tuberculosis prevention strategies [6]. However, another study by Tiemersma et al (2016) found that availability of infection prevention focal point person in health facilities encouraged health workers adherence to infection control principles and thereby reduced the risk of contracting tuberculosis and other infectious diseases when on duty [15]. Additionally, the current study found that nurses working at Namwala District Hospital had poor attitudes towards infectious disease prevention because they were not frequently wearing disposable hand gloves and face masks during their professional practice.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with a similar study by De Perio & Niemeier (2014) who observed that there was an increased risk of tuberculosis transmission when health workers practiced inadequate infection prevention strategies (6). However, another study by Tiemersma et al (2016) found that the availability of an infection prevention focal point person in health facilities encouraged health workers adherence to infection control principles and thereby reduced the risk of contracting tuberculosis and other infectious diseases when on duty (15).…”
Section: Discussionsupporting
confidence: 89%